Proximal and distal effects of genetic susceptibility to multiple sclerosis on the T cell epigenome - Tina Roostaei; Hans-Ulrich Klein; Yiyi Ma; Daniel Felsky; Pia Kivisäkk; Sarah M. Connor; Alexandra Kroshilina; Christina Yung; Belinda J. Kaskow; Xiaorong Shao; Brooke Rhead; José M. Ordovás; et al. (Nature Communications, 2021)
Integrating functional data with GWAS loci can help interpret the function of genetic variants associated with disease. Here the authors map cis and trans methylation QTL in CD4 + T cells from patients and colocalize with GWAS loci in order to interpret genetic variants associated with multiple sclerosis.